2012
DOI: 10.1016/j.jhealeco.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Economic booms and risky sexual behavior: Evidence from Zambian copper mining cities

Abstract: Existing studies suggest that individual and household level economic shocks affect the demand for and supply of risky sex. However, little evidence exists on the effects of an aggregate shock on equilibrium risky sexual behavior. This paper examines the effects of the early twenty-first century copper boom on risky sexual behavior in Zambian copper mining cities. The results indicate that the copper boom substantially reduced rates of transactional sex and multiple partnerships in copper mining cities. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 32 publications
(32 reference statements)
1
25
0
Order By: Relevance
“…While all these effects can have household-level implications, fewer analyses have, thus far, analyzed the geographic dispersion of such impacts. A recent literature on the local and subnational effects of natural resources contributes to the understanding of such effects (for example Rud 2013, 2015;Axbard et al, 2016;Benshaul-Tolonen 2018 Wilson 2012). A growing number of papers explore the mining industry, in particular, see Aragón, Chuhan-Pole, and Land (2015) for an overview.…”
Section: Introductionmentioning
confidence: 99%
“…While all these effects can have household-level implications, fewer analyses have, thus far, analyzed the geographic dispersion of such impacts. A recent literature on the local and subnational effects of natural resources contributes to the understanding of such effects (for example Rud 2013, 2015;Axbard et al, 2016;Benshaul-Tolonen 2018 Wilson 2012). A growing number of papers explore the mining industry, in particular, see Aragón, Chuhan-Pole, and Land (2015) for an overview.…”
Section: Introductionmentioning
confidence: 99%
“…They found that earnings decline with age, both among transactional sex workers and among women employed outside of transactional sex. Wilson (2012) provided a simple analysis of group means by age without including any controls. In a study of 248 transactional sex workers in The Gambia, Pickering et al (1992) found that younger transactional sex workers (e.g., under age 25) charged higher prices on average than did older transactional sex workers, yet was not able to examine how the likelihood of employment in transactional sex work varied with age.…”
Section: Conceptual Framework and Existing Evidencementioning
confidence: 99%
“…Zambia experienced a sharp increase in per capita income from mid‐2002 (Figure ) and a fall in poverty levels (CSO, ). Apart from Poverty Reduction Strategy Papers, copper production and earnings increased beginning late 2002, bolstered by the sharp rise in world copper prices (Wilson, ). On the micro level, as we shall see in the next section, average incomes increased.…”
Section: Settingmentioning
confidence: 99%
“…On the micro level, as we shall see in the next section, average incomes increased. Increases in employment and wealth as well as reduction in risky sexual behaviours for households located in mining towns have been documented (Wilson, ). This suggests that the copper boom may have changed household resilience to idiosyncratic shocks of one section of the population relative to others, for example, by changing relative incomes, risk behaviour and employment/occupations—likely related to likelihood of injury.…”
Section: Settingmentioning
confidence: 99%